Band alignment of cesium-based halide perovskites - Atchara Punya Jaroenjittichai (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. The perovskite Cs-B-X3(B = Ge, Sn, Pb and X = Cl, Br, I) compounds are currently in great interest because of their potentials to shape the progress of the third-generation photovoltaic cell. In such compounds, band offsets between their interfaces are vital parameters to enhance the electronic transport properties in the heterostructure devices. In this work, the band alignment of CsGeCl3, CsGeBr3, CsGeI3, CsSnCl3, CsSnBr3, CsSnI3, CsPbCl3, CsPbBr3and CsPbI3in the cubic phase were determined via density functional theory, using full potential linear muffin-tin orbital (FP-LMTO) within the single shot GW (G0W0) approximation. The dipole potential and the strain effect formed at the interface were determined from self-consistent supercell calculations under the framework of local density approximation (LDA). The straddling-type I alignment (of the “natural” band) was found among all Cs-B-X3interfaces except for CsSnBr3/CsSnI3, which is staggered-type II. However, after including the dipole potential (Vd) and strain induced potential (Vs), the type I changes to type II except for CsSnBr3/CsSnI3, which changes from type II to type I. This implies that the considered perovskite Cs-B-X3inherits many possible functional interface candidates for hole-electron separation (in different regions), which can be selective to suite desired solar cell applications.